2017
DOI: 10.1007/s00449-017-1774-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of lipase production by solid-state fermentation of olive pomace: from flask to laboratory-scale packed-bed bioreactor

Abstract: Lipases are versatile catalysts with many applications and can be produced by solid-state fermentation (SSF) using agro-industrial wastes. The aim of this work was to maximize the production of Aspergillus ibericus lipase under SSF of olive pomace (OP) and wheat bran (WB), evaluating the effect on lipase production of C/N ratio, lipids, phenols, content of sugars of substrates and nitrogen source addition. Moreover, the implementation of the SSF process in a packed-bed bioreactor and the improvement of lipase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Also, no significant differences in MC of fermented substrate at different conditions of air pressure and aeration rate were observed. Similarly, Oliveira et al . found equal lipase production by SSF in a packed‐bed bioreactor, using 25 g of substrate, at aeration rates of 0.05 and 0.1 L min ‐1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, no significant differences in MC of fermented substrate at different conditions of air pressure and aeration rate were observed. Similarly, Oliveira et al . found equal lipase production by SSF in a packed‐bed bioreactor, using 25 g of substrate, at aeration rates of 0.05 and 0.1 L min ‐1 .…”
Section: Resultsmentioning
confidence: 99%
“…SSF experiments were performed using OP mixed with WB, in a ratio of 1:1 (w/w, dry basis), 0.0133 g of (NH 4 ) 2 SO 4 per gram of dry solid substrate, 33.33 μL g ‐1 of inoculum solution with 10 7 spores mL ‐1 . The mixture of OP with WB resulted in optimum MC, of around 60% (w/w), without the need for its adjustment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many papers on lipase production using solid-state cultivation of fungi on different low-cost media derived from agroindustry residues have been published thus far, although no data of its successful commercialization on a large scale are available. With the purpose of lipase production, Aspergillus niger was cultivated on a variety of agricultural wastes [6][7][8][9], Rhizopus oryzae on sugarcane bagasse [10], Aspergillus species on olive pomace [11,12], Trichoderma strains on oil-palm fruit-bunch medium [13], Penicillium camemberti KCCM 11268 on wheat bran [14], Schizophyllum commune ISTL04 on Leucaena leucocephala seeds [15], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the lipase activity may not be oxygen-limited. Oliveira et al (2017) have reported an improvement in lipase activity in a culture of Aspergillus ibericus using wheat bran with 10% of olive oil as substrate applying an aeration rate of 2 mL min −1 g −1 . The authors reported that an aeration rate above 8 mL min −1 g −1 also has a negative effect on lipase activity and fungal growth was observed when they tested the SSF without aeration.…”
Section: Discussionmentioning
confidence: 99%